Motivational Impact of Four Algebraic Games on Students’ Interest in Algebraic Expressions - Ochulor, Humphrey Chinenye (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
Numerous studies have been conducted on mathematical games, but none have examined the best ways to mix different games to pique students' interest in algebraic expressions. The primary focus of this study was on how four algebraic games affected students' motivation and interest in algebraic expressions. The design for this study was a nonequivalent control group quasi-experiment. This gave room for a random partitioning of the students into experimental and control groups for proper treatment. For a comprehensive data collection in this study, a 380-sample size of junior secondary school students was purposively selected from two girls’ secondary schools and two boys’ secondary schools. The population from where the sample was obtained is 5,476 Junior Secondary School II students from 31 government schools in Enugu Education Zone. The normal mathematics instructors who worked with the students were research assistants. The inquiry was led by three hypotheses and two research questions. For analysis purposes, the study made use of the Algebra Interest Scale (AIS) for its data collection, while a reliability coefficient of 0.77 was determined by Cronbach’s Alpha. A 0.05 alpha level was obtained using Analysis of Covariance (ANCOVA) to test the hypotheses. The results of the study showed that the students who used the four algebraic games were more engaged, owing to their increased interest level, than those in the expository approach group. This proves that they were motivated to solve many algebra problems without coercion with the use of the four algebraic games. It was also obvious that the male and female students who used the four algebraic games showed gender parity in their interest ratings. Given that the findings favored the four algebraic games, the researcher recommended that mathematics teachers should undergo in-service training, conferences, seminars, and workshops, to be well-equipped for the effective use of these games in their classrooms.